(untitled) (Homiletic, 2025)
We live in times of strife, mainly due to cultural division and polarization in many countries, leading many to look to the Church for solutions. Although our faith calls us to Christian unity, our churches unfortunately remain divided along ethnic, tribal, religious, and political lines. The Sermon-Dialogue-Sermon (SDS) preaching method proposed by Leah D. Schade has proven effective in fostering collaboration and peacebuilding in divided regions. Having tested this method at Saint Charles Lwanga Parish in Yaoundé, Cameroon, and in various ministerial contexts across Cameroon, I propose the SDS method to equip preachers in Cameroon to mediate peace and build bridges of collaboration across the political divisions in this country.